Parenting to Reduce Child Screen Time: A Feasibility Pilot Study. Issue 1 (January 2018) - Sanders, Wesley; Parent, Justin; Forehand, Rex
ABSTRACT: Objective: Excessive screen time has been associated with a multitude of child health problems. This pilot study examined the feasibility and preliminary outcome of a novel 1-session intervention designed to help parents reduce their child's screen time. Methods: Thirty-nine parents of 5- to 12-year-old children were randomized to the intervention (a combined didactics and hands-on approach focused on technology-specific parenting) or waitlist control group. Results: The findings suggested that a sample could be recruited in a reasonable time (6 wk) at a reasonable cost, randomized, and retained at 6 weeks postintervention. Preliminary evidence suggested the intervention, which was implemented with fidelity, was associated with change in technology-specific parenting and 1 of 2 measures of child screen time. Parents reported satisfaction with the intervention and confidence in managing their child's screen time. Conclusion: The results of this pilot study suggest that this 1-session intervention is a promising approach to managing child screen time.